PENGARUH NORMA SUBJEKTIVE TERHADAP MINAT PEMBELIAN PRODUK SEPATU ADIDAS PALSU MELALUI SIKAP SEBAGAI VARIABEL MEDIASI STUDI KASUS MAHASISWA UNIVERSITAS NEGERI PADANG - Bilhuda, Ulwatul; Thamrin, Thamrin (Banking & Management Review, 2022)
This study aims to prove and analyze the effect of subjective norms on the purchase interest of fake Adidas shoes through variable attitudes. In this study, the samples were 100 active students at Padang State University. The process of testing the hypothesis is carried out using Smart PLS, namely through analysis of structural equation models (SEM). The testing process is carried out in two stages, namely looking for direct effects and looking for indirect effects of exogenous variables on endogenous variables which are strengthened by a mediating variable. Based on the results of testing the first hypothesis, it was found that subjective norms had a positive and significant effect on student buying interest at Padang State University on fake Adidas shoes. The second hypothesis testing of subjective norms has a positive effect on student attitudes at Padang State University on fake Adidas shoes. The third hypothesis is that attitudes have a positive and significant effect on student interest at Padang State University to buy fake Adidas shoes while the fourth hypothesis is that subjective norms have an effect on buying interest in fake Adidas shoes after going through attitude as an intervening variable for students at Padang State University.